Select and treat at laparoscopy and dye test improves the spontaneous pregnancy. (March 2014) - Younas, Kinza; Majoko, Franz; Sheard, Katherine; Edwards, Christopher; Bunkheila, Adnan
Abstract Infertility affects 1 in 7 couples in the UK. Tubal patency tests are an important part of infertility investigations. We conducted this observational study to determine the interval between a laparoscopy and dye test and spontaneous conception in women with unexplained infertility and minimal to mild endometriosis and pelvic adhesions treated during the procedure. The clinical records of 432 women coded as having had a laparoscopy and dye test or laparoscopy and tubal patency test between April 2007 and March 2010 were retrieved from a computerised theatre database. Pregnancies were identified through a computerised maternity booking system. Spontaneous pregnancies were recorded in 162 women following surgery (37.5%). There was a significant difference in conception rates between women with unexplained infertility and those with minor abnormalities treated at the time of diagnosis (43% vs. 58%, p = 0.019). Eighty percent of women who conceived spontaneously achieved their pregnancy within 18 months of surgery. A high proportion of women with unexplained infertility or minor abnormalities treated at the time of a laparoscopy and dye test conceived spontaneously within 12 months.